Spanish anarchist engagements in electoralism: from street to party politics. (2nd January 2018) - Ordóñez, Vicente; Feenstra, Ramón A.; Franks, Benjamin
Abstract: The eruption of the Spanish 15M movement in 2011 was marked by a high degree of political participation and creative experimentation. The political repertoire has constantly been re-evaluated, with methods revised and evolving, from the occupation of public spaces to the recent creation of new constitutional parties. One of the key aspects of these tactical revisions has been the involvement of anarchist actors in an experimental process of engagement in electoral processes, a method of political engagement anarchists standardly oppose. Our study identifies the motivations and theoretical justifications that have recently led libertarian activists to take the electoral path. This paper stands in the small but growing tradition of works that examine the recent phenomenon of new parties built by 'street' activists, but uniquely concentrates on a detailed case study of the anarchist actors linked to the platform Castelló en Moviment (CsM). It thus describes the anarchist influence in recent electoral developments, identifies proponents' justifications for engaging in these previously rejected methods and highlights some of the doubts raised about the electoral experiment.